1996
DOI: 10.1162/jocn.1996.8.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Dissociations in the Processing of “What” and “Where” Information in Working Memory: An Event-Related Potential Analysis

Abstract: Based on recent research that suggests that the processing of spatial and object information in the primate brain involves functionally and anatomically different systems, we examined whether the encoding and retention of object and spatial information in working memory are associated with different ERP components. In a study-test procedure subjects were asked to either remember simple geometric objects presented in a 4 by 4 spatial matrix irrespective of their position (object memory task) or to remember spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 41 publications
7
44
0
2
Order By: Relevance
“…Additionally, because a spatial dimension is essential for episodic memory, some studies have shown changes in the power and coherence of the EEG theta band during visuospatial learning in the central and posterior frontal regions. In fact, higher EEG theta power and coherence, predominantly in the 7.0-7.5-Hz frequency range, have been observed under intentional object position associations (Sato and Yamaguchi 2007) as well as under higher evoked potentials during object context associations (Mecklinger and Muller 1996). Nevertheless, EEG correlates of incidental visuospatial learning have rarely been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because a spatial dimension is essential for episodic memory, some studies have shown changes in the power and coherence of the EEG theta band during visuospatial learning in the central and posterior frontal regions. In fact, higher EEG theta power and coherence, predominantly in the 7.0-7.5-Hz frequency range, have been observed under intentional object position associations (Sato and Yamaguchi 2007) as well as under higher evoked potentials during object context associations (Mecklinger and Muller 1996). Nevertheless, EEG correlates of incidental visuospatial learning have rarely been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Results from monkey electrophysiology (Wilson, O'Scalaidhe, & Goldman-Rakic, 1993), experimental psychology (Della Sala, Gray, Baddeley, Allamano, & Wilson, 1999;Hecker & Mapperson, 1997;Smith et al, 1995;Tresch, Sinnamon, & Seamon, 1993), neuroimaging (e.g., Smith et al, 1995), human electrophysiology (Mecklinger & Muller, 1996), and human neuropsychology (Owen, Iddon, Hodges, Summers, & Robbins, 1997;Postle, Jonides, Smith, Corkin, & Growdon, 1997) confirmed the validity of this idea. The multiple component model was adjusted accordingly, with the visuospatial sketchpad divided into "visual cache" and "inner scribe" components for representing object and spatiotemporal information, respectively (Baddeley & Logie, 1999;Logie, 1995).…”
mentioning
confidence: 88%
“…Since spatial location was relevant to the correct response they were not pure Simon tasks, but hybrid spatial incompatibility tasks. There is evidence that the neural bases for working memory of object-appearance and spatial-location information are somewhat different (Haxby, Petit, Ungerleider, & Courtney, 2000;Levy & Goldman-Rakic, 2000;Mecklinger & Mueller, 1996) and spatial location is exactly the stimulus property that feeds the spatial-compatibility bias. In standard Simon tasks, subjects would perform better if they could (theoretically) screen out the location of the stimulus, but on our Dots and Arrows tasks information about the location of the stimulus is critical for determining the correct response.…”
Section: How Our Predictions Concerning Memory and Inhibition Faredmentioning
confidence: 99%